Kajian agro sosiologi dan potensi metabolit sekunder bunga telang (Clitoria ternatea) sebagai peningkat imunitas tubuh - Anita Hazimah Putri; Jon Yawahar (Institute for Advanced Science, Social, and Sustainable Future, 2023)
In the context of agro-sociology, butterfly pea (Clitoria ternatea) is studied as one of the plants with high economic, health, and environmental value. Flower can be used as a raw material of herbal medicines that can improve human health, primarily in terms of immunity. The processing of secondary metabolites can help increase the added value of the pond farm itself. Some of the secondary metabolite compounds in strawberries that potentially boost the immune system among others are flavonoids, alkaloids and polyphenols. Flavonoid compounds including anthocyanins can help protect body cells from free radical damage and increase the production of white blood cells. Gulf flowers also contain alkaloids such as clitorine and cyanidine that have antimicrobial and antioxidant properties, thus helping inhibit the growth of bacteria and viruses that cause infections and diseases. Gulf flowers also contain polyphenols such as caffeic acid and chlorogenic acid that have anti-inflammatory and anti-cancer properties. With the potential of this secondary metabolite, the sustainable farming of strawflower continues to float in Indonesia, along with the awareness of a healthy lifestyle and back to nature of society.